Children's Initial Understanding of the Related Meanings of Polysemous Noun-Verb Pairs. Issue 3 (2nd July 2020) - Lippeveld, Marie; Oshima-Takane, Yuriko
ABSTRACT: The cross-categorical use of nouns and verbs poses a challenging problem to young language learners because they are known to be less willing to accept that a single form of a word be used for more than one linguistic purpose (e.g., one-form/one-function principle). The present study investigated whether children under 3 years of age are able to quickly understand the cross-categorical use of object-function denoting nouns (e.g., This is a nice brush ) as denominal verbs (e.g., Brush your teeth ) when the semantic relationship between the objects, referred to by the nouns, and their functions, referred to by the denominal verbs, is transparent. French-speaking 2.5-year-olds were taught the cross-categorical use of three novel parent noun and denominal verb pairs by presenting these pairs with semantic information coupled with noun and verb distributional cues. The results from Experiment 1 showed that, contrary to the one-form/one-function principle, 2.5-year-old children were able to fast-map the novel object-function noun-verb pairs onto novel objects and actions they had never seen before after three exemplars were shown. However, the results from Experiment 2 indicated that after being taught the cross-categorical use of two novel object-function noun-verb pairs, 2.5-year-olds were not able to interpret the third novel object-function noun-verb pair correctly when it was presented with semantic information coupled with noun distributional cues only. These findings suggest that although 2.5-year-olds do not have a strong one-form/one-function mapping constraint, they are not able to quickly form abstract class extension rules that enable them to immediately understand the cross-categorical use of new noun-verb pairs they have not heard before.